2005
DOI: 10.1242/jcs.01695
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate induces cytoskeletal reorganization in C2C12 myoblasts: physiological relevance for stress fibres in the modulation of ion current through stretch-activated channels

Abstract: Sphingosine 1-phosphate (S1P) is a bioactive lipid that is abundantly present in the serum and mediates multiple biological responses. With the aim of extending our knowledge on the role played by S1P in the regulation of cytoskeletal reorganization, native as well as C2C12 myoblasts stably transfected with green fluorescent protein (GFP)-tagged α- and β-actin constructs were stimulated with S1P (1 μM) and observed under confocal and multiphoton microscopes. The addition of S1P induced the appearance of actin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 46 publications
6
75
0
Order By: Relevance
“…Electrode capacitance was compensated before disrupting the patch. All the passive properties parameters were estimated as in Formigli et al [25]. All experiments were performed at room temperature (20-23°C).…”
Section: Electrophysiological Studiesmentioning
confidence: 99%
“…Electrode capacitance was compensated before disrupting the patch. All the passive properties parameters were estimated as in Formigli et al [25]. All experiments were performed at room temperature (20-23°C).…”
Section: Electrophysiological Studiesmentioning
confidence: 99%
“…mobilization [6,8,9], actin cytoskeletal remodeling, and mechanosensitive stretch-activated cation channel (SAC) opening [10,11]. The formation of stress fibers by S1P has been associated with plasma membrane stretching and, in turn, with SAC activation in C2C12 myoblasts [12,13]. Several members of the transient receptor potential canonical (TRPC) ion channel family are recognized as promising candidates for SACs in different cell types [14], including sensory neurons [15], vascular smooth muscle [16], endothelial cells [17], and skeletal myoblasts [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the measurement of accurate mechanical parameters is of extreme importance, the idea of controlling and altering biological pathways is equally enticing. Previously, it has been shown that mechanical force delivered by the AFM tip can induce various chemo-mechanical responses [167][168][169]. In recent work, it has also been shown that the mechanical environment of many cell types (including cancer and stem cells) can be used to control and alter gene expression and differentiation pathways [21-25, 164,170,171].…”
Section: Introductionmentioning
confidence: 99%